Experience in conducting clinical trials in Cienfuegos - Olga Lidia Cuevas Pérez; Diana Rosa Fernández Ruíz; Gredsy Escandón López; Mayra Quirós Enrique; Yuleidis García Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: Cienfuegos is inserted in the National Netork of Clinical Trials of the nineties. Decade. It has an important parrticipation in the registration of new drugs, which up to the moment has not been enough disseminated. This is the reason of the importance of showing the growth achived in the province in this activity. Objective: To describe the experience and development achived in Cienfuegos in conducting clinical trials. Methods: it is a descriptive study on the clinical trials conducted in Cienfuegos from May 1992 to May 2016. Variables such as: promoting center, evaluated product, stage of the clinical trials, medical specialties and number of patients included were analyzed. Results: a number of 64 clinical trials were carried out, basically form Center for Genetic Engineering and Biotechnology and the Center of Molecular Inmunology. The medical specialties with most participation were oncology and hematology with 15 (23.4%) and 10 (15.6%) trials respectively. The highest percentage of research were aimed at confirming the efficacy and safety of product for the treatment of cancer. with the conduction of 30 clinical trials (46.8%) in locations as lungs, hematologic system, breast, head and neck and prostate. A number of 2420 patients were included. There implementation extended to the Primary Health Care System and the Gustavo Aldereguia Lima Provincial Hospital was incorporated to the process of certification. Conclusion: There is a systemtic work in Cienfuegos related to the conduction of clinical trials. There has been a contribution and comercialization of several products.